PEREMPUAN DAN GAYA HIDUP BARAT DI KOTA YOGYAKARTA PADA AWAL KEMERDEKAAN INDONESIA - Hervina Nurullita; Hendra Afiyanto (Handep: Jurnal Sejarah dan Budaya, 2021)
The article came as the inheritance reconstruction of the colonial effect phenomenon in Yogyakarta after the declaration of independence. It is interesting to discuss how the people of Yogyakarta show an anti-Netherland attitude toward colonial heritage, which is interpreted widely as anticolonial and anti-Netherland, but accept western lifestyle in daily life. The spread of western lifestyles makes Yogyakarta women begin to reconstruct culture to look for a new identity in their life which is paradoxical with the mainstream attitude and behavior of Yogyakarta people at the beginning of Independence Day. The paper aims to explain the acceptance of women in Yogyakarta to western lifestyles in daily life amidst the strengthening of anti-western sentiment. This paper presents the historical study result using the historical method with the stage of heuristics, criticism, interpretation, and historiography. This study used modernization theory. Modernization has a significant influence on the easy access of women in Yogyakarta to keep up with the times. The study shows how western lifestyles grew and became a trend of women’s appearance in Yogyakarta at that time.